1994
DOI: 10.1139/x94-243
|View full text |Cite
|
Sign up to set email alerts
|

Fungal sporocarp mediated losses of Ca, Fe, K, Mg, Mn, N, P, and Zn from conifer logs in the early stages of decomposition

Abstract: The export of mass and nutrients associated with the formation of fungal sporocarps during the first 7 years of decomposition of logs of four conifer species (Abiesamabilis Dougl. ex Forbes, Pseudotsugamenziesii (Mirb.) Franco, Thujaplicata D. Don, and Tsugaheterophylla (Raf.) Sarg.) was investigated in western Oregon. Abundance of the most common fungal species, Naematolomacapnoides (Fr.:Fr.) P. Kumm, differed significantly with log species; the fungus was most abundant on Abies and least abundant on Thuja. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(12 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Even though fungi are efficient in recycling wood N (Stenlid, Penttilä & Dahlberg ), some N may be lost when sporocarps are consumed or drop on the forest floor after death (Harmon et al . ). Similarly, fragmentation, which tends to remove the most decayed and thus most nutrient‐rich parts of logs, may transfer significant amounts of N to the forest floor (Harmon et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though fungi are efficient in recycling wood N (Stenlid, Penttilä & Dahlberg ), some N may be lost when sporocarps are consumed or drop on the forest floor after death (Harmon et al . ). Similarly, fragmentation, which tends to remove the most decayed and thus most nutrient‐rich parts of logs, may transfer significant amounts of N to the forest floor (Harmon et al .…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, fragmentation, which tends to remove the most decayed and thus most nutrient‐rich parts of logs, may transfer significant amounts of N to the forest floor (Harmon et al . ). In addition, atmospheric N deposition could have been a minor source of N for decayed wood in this study site (Bebber et al .…”
Section: Discussionmentioning
confidence: 97%
“…Concentrations of PO 4 + DOP in these collectors averaged 437 (Jig L~' for 120 d after appearance and decay of the sporocarps vs. 89 (xg L~' in these same collectors at other periods. Harmon et al (1994) found that concentrations of P in sporocarps were about 9 to 100 times those in undecayed logs and they concluded that sporocarp formation was the main pathway of loss of N and P from logs during the first few years of decomposition.…”
Section: Sources Of Dissolved Organic Matter Above the Mineral Soilmentioning
confidence: 99%
“…Many factors influence EM fungal community structure, including host plant species composition and stand age, habitat conditions, and edaphic factors (Molina and Trappe 1982;Deacon et al 1983;Vogt et al 1992;Visser 1995;States and Gaud 1997;Gehring et al 1998;Claridge et al 2000;Smith et al 2000). Down wood in various stages of decay influences fungal species occurrence and abundance (Harmon et al 1994;Smith et al 2000). Changes in plant species composition from forest succession or large-scale disturbances significantly affect EM species composition and total sporocarp production (Cooke 1955;Dighton and Mason 1985;Arnolds 1988Arnolds , 1991Termorshuizen 1991;Vogt et al 1992;Amaranthus et al 1994;Visser 1995;North et al 1997;Waters et al 1997;Baar et al 1999;Colgan et al 1999).…”
Section: Introductionmentioning
confidence: 99%